A gamificação no processo de aprendizagem de LIBRAS - Rios, Lucas Tadeu Rosente (2017)
This research aims to study the development of gamified interfaces for bilingual literacy for deaf children, with LIBRAS as their first language and Portuguese as the second language. The study on the deaf individual was motivated by the need to know better the characteristics of the target audience of this research. We ought to explore the definition of deafness, how we classify hearing loss and the deaf individual, and the characteristics of this individual, especially children, in the emotional aspects, focus and attention, and acquisition of vocabulary. The research also has the focus of studying the process of bilingual literacy of the deaf subject and the difficulties presented during the learning. Also in this context, we seek to investigate the education and the bilingual literacy process of deaf children and to point out the main characteristics and difficulties in the teaching and learning of LIBRAS as first language and Portuguese as a second language. In a second moment, the research brings to the discussion the analysis and the application of gamification within the school context. We study the application of gamification within this teaching environment, trying to understand the difficulties, needs and effective learning opportunities that the use of games can provide. Finally, we propose a reflection on the influence of the use of these technologies on the behavior and social relation of the deaf individuals, as well as the survey of the main educational technologies developed exclusively for mobile devices with the intention of teaching LIBRAS. Also in this context, through the analysis of the researched material, we try to discuss and suggest some best practices for the development of educational game interfaces for this target audience